2011
DOI: 10.7599/hmr.2011.31.2.70
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Therapy for Chronic Nonmaliganat Pain

Abstract: While acute pain is reasonably considered a symptom of disease or injury, chronic pain is a specific healthcare related problem as a disease in its own right. Even though the use of opioids in the management of chronic cancer pain has been growing, the chronic use of opioid medication for nonmalignant pain is still controversial. Most reports suggest that chronic opioid therapy can be effective for the reduction of chronic pain and for the improvement of function and health related quality of life. On the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Second, data analyzed in this study are based on reimbursement claims, meaning that any opioids prescribed outside of the national insurance market would not be recorded. This could result in an underrepresentation of actual opioid prescription quantities [ 53 ]. Third, the diagnostic codes assigned to patients may not always be completely accurate, which could impact the accuracy of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Second, data analyzed in this study are based on reimbursement claims, meaning that any opioids prescribed outside of the national insurance market would not be recorded. This could result in an underrepresentation of actual opioid prescription quantities [ 53 ]. Third, the diagnostic codes assigned to patients may not always be completely accurate, which could impact the accuracy of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although opioid therapy is highly effective in pain management, the risk of side effects is substantial, highlighting the necessity for serious consideration of potential harm [ 31 ]. In a previous study, patients aged >65 years with chronic musculoskeletal pain who used opioids reported that the risk of adverse events was three times higher than that of the control group, but opioids only had a small effect on decreasing pain intensity [ 32 ].…”
Section: Discussionmentioning
confidence: 99%